Coprorate Image Analysis on The Implementation of Community Relations Programs by PLN - Prihastiti, Nurdini; Indah Kusumastuti, yatri (Sodality: Jurnal Sosiologi Pedesaan, 2012)
A company will be able to survive if it has a good corporate image in the public. Public relations in every company is important to have the right strategies. To maintain coporate sustainibility, required relations between company with the community as an external public through community relations. PLN as a state company in charge of providing the power supply to all regions in Indonesia, run a community relations with the community in an area that has not received the power supply with Micro-hydro Power Plant (PLTMH) Programs. One of the PLTMH program is made in Lebak Picung. This study aims to determine the implementation of the community relations programs by PLN in Lebak Picung, as well as analyzing the relationship of community relations program with the process of corporate image building, and analyze the process of corporate image with PLN’s corporate image formed on community that received PLTMH program in Lebak Picung. Data is collected by census at all household and the respondents are the head of family or member who can represent of all members in the house. Data obtained thorough observation, in depth interviews and interviews using a questionnaire. The overall question in the quesionnaire using an ordinal scale then continued on correlations test. The results show the influence of respondent in the brand image building process is the judgementto the benefits. Respondent’s involvement in the program was not shown  to have influence in corporate image process.  In addition, there is a positive relationship between the process of corporate image that forms on the respondent. The more respondent rated PLTMH program provides positive benefits, the level of exposure, attentions and comprehensive of the responden are also tends to be high. Companies need to consider that the empowerment program should consider the needs of the targets, so the programs can be mutually beneficial. The company has a very positive image in the public so it maintain continuity of businessand community needs as program beneficiaries are met.